PERKEMBANGAN PERSYARIKATAN DAN AMAL USAHA MUHAMMADIYAH CABANG MERDEN PURWANEGARA BANJARNEGARA - Isria Rizqona Firdausyi (Khazanah Pendidikan, 2017)
The aim of this research is to determine the general condition of Purwanegara District Banjarnegara Regency, the development of Muhammadiyah organization branch Merden up to 2013, and the bussiness charity of Muhammadiyah organization branch Merden in education and non education fields. This study used historical method. The result showed that Muhammadiyah Branch Merden intially established as a group Muhammadiyah which was under Purbalingga Branch, only a year later it became Banjarnegara Branch. Then, in the fourth period of Abu Dudjanah leadership, group of Muhammadiyah Branch Merden changed into Muhammadiyah sub-section, and in the next period turned into a branch of Muhammadiyah up to now with various business charities both in education and non-education fields. Keywords: Muhammadiyah organization, social history, business charity of Muhammadiyah